Peran Guru dalam Meningkatkan Motivasi Belajar Peserta Didik di SD Negeri 34/I Muara Bulian - Pertiwi, Diah; Putri, Riska Adinda; Neli, Neli; Febriani, Febriani; Puspitasari, Diah Eka; Melhana, Melhana (ANWARUL, 2022)
Education is a conscious effort to grow the potential of human resources through teaching activities. Even in elementary school, student motivation in learning is one of the keys to achieving success in learning. Currently, many students are less motivated to learn. In this research, research was conducted on the teacher's role in increasing the learning motivation of students at SD N 34/I Muara Bulian. In this study researchers used qualitative research. This research was conducted by obtaining data sources as complete as possible in real terms, then researchers obtained information related to the teacher's role in increasing students' motivation to learn. The focus of this research is related to the teacher's role in increasing learning motivation. This study uses a phenomenological design where the phenomenological research design reveals things through phenomena that occur directly. The research location is located at SD Negeri 34/I Muara Bulian. Based on the results of the research that has been done, it can be concluded that the role played by the teacher in increasing student learning motivation at SDN 34/I Muara Bulian is the teacher as a demonstrator, class manager, mediator, facilitator, motivator, and evaluator.